A traveller in thirteenth-century Arabia : Ibn al-Mujāwir's Tārīkh al-mustabṣir - Ibn al-Mujāwir, Yūsuf ibn Yaʻqūb, 1204 or 1205-1291 or 1292.; Smith, G. Rex (Gerald Rex); Hakluyt Society (Aldershot, England ; Burlington, VT : Ashgate, 2008)
"This is the first English translation of the Tarikh al-Mustabsir, written in the early quarter of the thirteenth century by Ibn al-Mujawir. The text is a fascinating account of the western and southern areas of the Arabian peninsula by a man from the east of the Islamic world, probably from Khurasan in Iran." "Ibn al-Mujawir was a man who in all probability followed the age-old Islamic practice of making the pilgrimage to Mecca and thereafter travelling in the area to further his business interests. His route began in Mecca and essentially ran south through the Red Sea coastal plain, Tihamah, down into the Yemen and along the southern coast of the peninsula. He paused long in Aden, where he observed closely the activities of the port to report at some length on its administration, its taxes, its markets, its currency, its weights and measures, and the like. His route then continued along the southern coast of Arabia and into the Gulf, and he presumably returned home to the east via Iraq. The author is a wonderful observer of people: their buildings, their dress, their customs, their agriculture, their food and their history." "This book is a unique source for the social and economic history of thirteenth-century south Arabia, written with a humour and wit otherwise unknown in the writings of medieval Islam. The text is of major linguistic importance, too, written as it is in a far from classical Arabic. This translation is fully annotated with an introduction, appendices, glossary and full index, and contains maps and illustrations."--Jacket
Ibn al-Mujāwir's introduction -- Ibn al-Mujāwir's route descriptions -- Ibn al-Mujāwir's parasang -- Place names -- Agriculture, crops, fruits, vegetables and food -- dress and social customs -- Magic, the wondrous and the bizarre -- Hstory and buildings -- Maps and plans and diagrams in the text -- Trade and commerce -- Source of social and economic history of Arabia -- Assessment of the contents.
Includes bibliographical references (pages 311-324) and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
Translated from the Arabic.
Keywords: Yemen (Republic) -- Description and travel -- Early works to 1800.; Mecca (Saudi Arabia) -- Description and travel -- Early works to 1800.; Saudi Arabia -- Description and travel -- Early works to 1800.; Yémen -- Descriptions et voyages -- Ouvrages avant 1800.; La Mecque (Arabie Saoudite) -- Descriptions et voyages -- Ouvrages avant 1800.; Arabie Saoudite -- Descriptions et voyages -- Ouvrages avant 1800.; TRAVEL -- Asia -- General; Travel; Saudi Arabia; Saudi Arabia -- Mecca; Yemen (Republic); Electronic books; Early works